1+tan^2A/1+cot^2A = (1-tanA/1-cotA) to prove this
plz ans fast I have to submit tomorrow only plz jaldi
Answers
Answered by
1
(1+ tan2A) / (1+ cot2A)
= (1+ tan2A) / (1+ 1/tan2A)
= (1+ tan2A) / [(tan2A+ 1)/tan2A)]
= tan2A
I think ....
= (1+ tan2A) / (1+ 1/tan2A)
= (1+ tan2A) / [(tan2A+ 1)/tan2A)]
= tan2A
I think ....
niharika44:
ya u r ans is right I'm sorry I was confused
Answered by
3
HEYA!!
YOUR SOLUTION IS IN THE ATTACHMENT.
LHS= RHS
HENCE, PROVED.
#KEVIN
HOPE IT HELPS YOU ☺
YOUR SOLUTION IS IN THE ATTACHMENT.
LHS= RHS
HENCE, PROVED.
#KEVIN
HOPE IT HELPS YOU ☺
Attachments:
![](https://hi-static.z-dn.net/files/d29/e6e298d799454922a861d99c9540991f.jpg)
Similar questions